Comparative analysis indicates regulatory neofunctionalization of yeast duplicates - Tirosh, Itay (BioMed Central, 2007)
BACKGROUND: Gene duplication provides raw material for the generation of new functions, but most duplicates are rapidly lost due to the initial redundancy in gene function. How gene function diversifies following duplication is largely unclear. Previous studies analyzed the diversification of duplicates by characterizing their coding sequence divergence. However, functional divergence can also be attributed to changes in regulatory properties, such as protein localization or expression, which require only minor changes in gene sequence. RESULTS: We developed a novel method to compare expression profiles from different organisms and applied it to analyze the expression divergence of yeast duplicated genes. The expression profiles of Saccharomyces cerevisiae duplicate pairs were compared with those of their pre-duplication orthologs in Candida albicans. Duplicate pairs were classified into two classes, corresponding to symmetric versus asymmetric rates of expression divergence. The latter class includes 43 duplicate pairs in which only one copy has a significant expression similarity to the C. albicans ortholog. These may present cases of regulatory neofunctionalization, as supported also by their dispensability and variability. CONCLUSION: Duplicated genes may diversify through regulatory neofunctionalization. Notably, the asymmetry of gene sequence evolution and the asymmetry of gene expression evolution are only weakly correlated, underscoring the importance of expression analysis to elucidate the evolution of novel functions.